Penerapan Strategi Pembelajaran Problem Based Learning Terhadap Kemampuan Kreatif Peserta Didik - Dwi Fitri Yani; Siti Tiara Maulina (Shofanah Media Berkah, 2023)
Source power human that quality tall Marked with Skills Management, use and Develop power thinkwrong Only think creative. Development Skills think creative Needed to help solve problem and look for alternative Solving problem. Ability think creative will become food Later Face Various Problems that exist, Especially In the era of globalization. Attempt that get Done Strengthening ability think creative Done through education. Purpose research .ini be to know Application Strategy Learning Problem Based Learning Towards Ability Creative Participants Educate. Method research that Used Descriptive Qualitative with Engineering Collection data Study Library with read and Analyze Articles, journalsand book. PBL Viewed as type Learning that can Increase ability think level tall or ability think creative. Ability think creative Influenced by encouragement internal and External. Personality and Background back culture somebody get affect attempt somebody to think creative towards one problem life. With Learning Based Problem Based Learning Expected teacher or lecturer become facilitator best for Participants educate and studentsand student Expected can Communicate with good and think creative deep Settlement problem Keywords: Think creatively, Problem Based Learning